2023
DOI: 10.3233/wor-220205
|View full text |Cite
|
Sign up to set email alerts
|

Safety behavior of agricultural workers around face mask-wearing during the COVID-19 pandemic

Abstract: BACKGROUND: Agricultural labor-intensive activities have been threatened by COVID-19. Wearing a face mask has been introduced as one of the personal protective equipment (PPE) to reduce COVID-19 risk. OBJECTIVE: The present study aimed to investigate the safety behavior of urban green space workers around wearing a face mask in the time of COVID-19 before vaccination. METHODS: The personal and safety backgrounds of 61 male participants were collected using a designed questionnaire. The nonparametric correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Further, the odds of using PPE were found to be substantially lower among the farmers who were involved in farming for more than 10 years. A similar finding was seen in a study conducted in India where the farmers who had mean 18 years old farming exposure were not following safety practices [29]. This could be because those farmers may have developed sense of confidence in their work and have less perceived risk in their work by underestimating the potential hazard of pesticide and have a false belief that they can manage the risk without the use of PPE.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…Further, the odds of using PPE were found to be substantially lower among the farmers who were involved in farming for more than 10 years. A similar finding was seen in a study conducted in India where the farmers who had mean 18 years old farming exposure were not following safety practices [29]. This could be because those farmers may have developed sense of confidence in their work and have less perceived risk in their work by underestimating the potential hazard of pesticide and have a false belief that they can manage the risk without the use of PPE.…”
supporting
confidence: 76%
“…The COVID pandemic heightened the awareness about PPE for disease prevention and led to the heightened demand and usage of PPE. The increase in production and distribution led to an increased availability, leading to an increased proportion of PPE use among farmers in our study [29]. However, it is contradicting, as our study also showed that more than half of the population of farmers do not use basic set of PPE while handling pesticides, which implies that farmers in Nepal are still at high risk of developing various pesticide-related-illnesses.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations